Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Budaya Organisasi, Sistem Pengembangan Dan Komitmen Organisasional Terhadap Kinerja HMJ Manajemen ITS Mandala - Zainal; Nely Supeni; Muhdar (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of Leadership Style, Work Motivation, Organizational Culture, Development System and Organizational Commitment on the Performance of HMJ-MANAJEMEN ITS MANDALA. The data of this study were obtained from the distribution of Questionnaires to the research objects with a sampling technique using Non-Probability, namely selecting samples based on certain criteria that are relevant to the research objectives. This type of research is quantitative. The sample used in this study were members of HMJ-MANAJEMEN ITS MANDALA with a total of 100 respondents. Data analysis used Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Determination Coefficient Test (R²), t Test and F Test Using SPSS 20. The results of this study indicate that the Leadership Style variable does not have a partial effect on the Performance of HMJ-MANAJEMEN ITS MANDALA. While Work Motivation, Organizational Culture, Development System, and Organizational Commitment partially have a significant effect on the performance of HMJ-MANAJEMEN ITS MANDALA. And simultaneously the variables of Leadership Style, Work Motivation, Organizational Culture, Development System and Organizational Commitment have a significant effect on the Performance of HMJ-MANAJEMEN ITS MANDALA.